2020
DOI: 10.14710/nmjn.v10i2.29117
|View full text |Cite
|
Sign up to set email alerts
|

Does Tabletop Exercise Enhance Knowledge and Attitude in Preparing Disaster Drills?

Abstract: Background: Tabletop Exercise (TTE) is a specific learning method through a simulation designed to test the competency and the ability of a group to respond to disasters. Using the map of disaster events is considered effective to prepare disaster drills rather than other methods. TTE method has been carried out annually to train the students, however no studies reported the effect of this method.Purpose: The study aimed to evaluate the effect of TTE on enhancing nursing students’ knowledge and attitude in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Four studies found that tabletop exercises were valuable and recommended their inclusion into nursing programs as an educational tool. 6,[8][9][10] One study recognized that the tabletop exercise helped identify gaps in the content of the nursing program, specifically the medical-surgical courses that prepared students for disaster management. 5 Three studies identified that the tabletop exercise improved the students' knowledge and attitudes of disaster planning based on pre-and postexercise coursework.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Four studies found that tabletop exercises were valuable and recommended their inclusion into nursing programs as an educational tool. 6,[8][9][10] One study recognized that the tabletop exercise helped identify gaps in the content of the nursing program, specifically the medical-surgical courses that prepared students for disaster management. 5 Three studies identified that the tabletop exercise improved the students' knowledge and attitudes of disaster planning based on pre-and postexercise coursework.…”
Section: Review Of Literaturementioning
confidence: 99%
“…5 Three studies identified that the tabletop exercise improved the students' knowledge and attitudes of disaster planning based on pre-and postexercise coursework. [8][9][10] Tabletop Disaster Planning Exercise…”
Section: Review Of Literaturementioning
confidence: 99%
“…It systematically investigates and indicates how well the exercise met its objectives. It also determines the strengths and weaknesses of the disaster exercise program [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many financial resources are spent in the health sector on disaster preparedness exercises. As there is no plan to control such exercises and they are not evaluated accurately to identify the strengths of organizations executing exercises, macro targeting and perspectives on health system preparedness in unexpected events have not been achieved, and they have not been measured scientifically [ 13 , 19 ]. The above emphasizes the design and development of a comprehensive tool for evaluation of disaster exercises in the healthcare system in the exercise design phase to provide necessary protocols and instructions for evaluating disaster preparedness exercises.…”
Section: Introductionmentioning
confidence: 99%
“…These disasters are the evidence of the country’s high vulnerability to such events (Badan Nasional Penanggulangan Bencana Aceh/National Board for Disaster Management of Aceh, 2015). Disasters cause physical harm, injury, disability, death of humans and economic problems, therefore, all elements of society have an important role to play before, during and after an incident (Bazyar et al , 2020; Husna et al , 2020b). However, Husna et al (2020c) argued that even though such incidents occur periodically, the preparedness of the community, government and disaster management agencies in responding to a disaster remains inadequate.…”
Section: Introductionmentioning
confidence: 99%